İLKÖĞRETİM 6. , 7. VE 8. SINIF TÜRKÇE DERS KİTAPLARINDA YER ALAN YABANCI KELİMELER ÜZERİNE BİR DEĞERLENDİRME - ECE, MİNE (Fırat Üniveristesi, 2008)
insanlar arasındaki iletişimi en iyi şekilde sağlayan canlı bir varlık, kültürün aktarıcısıdır. Milleti millet yapan en önemli öge olup toplumun bütünlüğünün de sağlayıcısıdır. Dilin sözvarlığı içinde birçok unsur yer alır, bu unsurlardan biri de yabancı kelimelerdir. Dile çeşitli sebeplerle dışarıdan gelen ve çoğunlukla ihtiyacı karşılayan bu kelimeler her milletin dilinde belli oranda görülmektedir. Toplumlar arası etkileşim engellenemeyeceği için diller arası kelime alışverişi de her zaman olacaktır. Türkçenin de tarihi gelişim ve değişimine bakıldığında Türkler, yaşadıkları değişik coğrafyalarda komşuluk ettikleri farklı milletlerin dilinden kelime alışverişi yapmışlardır. Bu alışverişte sıkça din ve alfabe değiştirmeleri de çok etkili olmuştur. Türkçede yer alan yabancı kelimelerin Türkçe ders kitaplarındaki oranı, doğu-batı dillerinin dildeki ağırlığı ve bu kelimelerin görev ve yapıları üzerinde durulduğunda yabancı kökenli kelimelerin Türkçenin tarihi süreç ve kullanım durumu süzgeçlerinden geçerek dile sıkıca yerleştiği görülür.Anahtar Kelimeler: Dil, yabancı kelime, doğu-batı dilleri, Türkçe ders kitapları.

Language is a living being enabling communication among people in the best way, the transmitting-medium of a culture. It is the most significant component forming a nation, and it enables the integrity of a society. There are a great many components in the vocabulary of a language, and one of these components is borrowed words. These words, which get into a language from outside for some reasons and which answer the needs of that language most of the time, can be observed in every language to some extent. As the interaction among the societies cannot be hindered, there will invariably be the vocabulary interchanges among languages. When the historical development and variation of Turkish language is examined in this sense, it can also be seen that Turks have borrowed words from the languages of different nations of a diverse geographical neighbourhood they have lived in. A frequent religion and alphabet change of them has also been effective in this interchange. When the proportion of these borrowed words in Turkish language subject books, the dominance of the eastern and western languages in Turkish, and the functions and structures of these borrowed words are examined, it is witnessed that these borrowed words have settled firmly in the language by undergoing through the filter of the historical process and pragmatics of Turkish.Key Words: Language, Borrowed Words, Eastern-Western Languages, Turkish Language Subject Books.
An evaluation of foreign words used in sixth, seventh and eighth grade Turkish language textbooks
Keywords: Eğitim ve Öğretim